(untitled) (Tanzania Journal for Population studies and Development, 2024)
Internal and external migrations differ significantly in their social, economic, and environmental drivers; as well as their impacts on individuals and regions. This article critically assesses the socio-economic and environmental drivers of internal migration, alongside its effects in Morogoro Municipality, Tanzania. A cross-sectional study was conducted utilizing a purposive sample of 201 internal migrants from three wards. Data was collected through a mixed-methods approach that incorporated both quantitative and qualitative techniques. Quantitative data was analysed using descriptive statistics, while qualitative data was examined thematically for deeper insights. The findings revealed that 60% of the migrants were rural-urban movers, primarily originating from Dodoma region. Employment opportunities (34%) and business prospects (31%) emerged as the primary drivers of this migration. However, the rapid population growth resulting from these movements has placed significant pressure on local services, particularly in water supply, market facilities, and waste management. Markedly, 82% of respondents identified inefficient collection of household waste as a major challenge, underscoring the strain on the waste management system. This article concludes that while internal migration contributes to economic diversification and demographic changes in Morogoro Municipality, it has also intensified demands on infrastructure and public services. Therefore, it is crucial for local authorities to prioritize investment in infrastructure, especially in water supply and waste management systems. Comprehensive urban planning is essential to balance residential and commercial development, while safeguarding environmental resources. Similarly, policymakers are urged to adopt strategic approaches to effectively manage the impacts of internal migration, and promote sustainable urban development.